Kimberly Orrell: capstone - Orrell, Kimberly, artist (Colorado State University. Libraries, 2013)
The artist's statement: As a fiber artist, I am drawn to domestic textiles because they reference tradition and lineage; they tell the story of our daily lives. The materials I work with are the type of things found in your linen closet: sheets, blankets, and handkerchiefs... I see them as a vehicle for talking about gender and identity. In my work I share experiences from my life in order to show how my female experiences speak of the human condition. I address difficult topics like illness and abuse because I want to give voice to these things that are shrouded in silence and shame. These aren't just my stories, they are everyone's. I am a bit of a Magpie, I collect things, without knowing why they are important; I just know I have to have them. Eventually their purpose is revealed. As in, Surrender Is Not Consent, this double, top sheet came my way, having been discarded. It is the stains and the archaic size that make it appealing to me. This history, the secrets that this cloth harbors, make it the perfect ground for a piece about sexual assault. These found materials have a will of their own, and I am required to yield to it; it is collaboration, we respond to each other. We wrestle as we learn the other's limitations. This part of my process is meditative. I love the quiet solitude of making. Intense focus charges my work, infusing it with my emotional energy. As the cloth passes through my hands I realize the depth my piece is capable. With every action I stitch in hope and promise and heart, lovingly. I am not interested in perfection. My individual mark is evidence of my existence, and distinguishes my work from mass produced, cold, machine made products. My ideas usually come to me when I'm doing something else, the day-today mundane things. I allow the idea to speak to me. Sometimes it is material that triggers the story, like with Transition Object. I found this soft wool yarn... the color, the texture; it was so familiar. There was something about it that spoke to me of the past, and I knew I had to weave a blanket like the one I had as a child. The object is a vehicle for the story; I make the object and it tells the story. Sometimes things are so commonplace, we have to see them compiled in a series of multiples, in a heap of objects, in order to realize their significance. Reckless Hope or Denial, is an installation compiled of many red flags stung together like Tibetan Prayer Flags. Together, they take over a space, both physically and with their bold color. I am constantly adding more flags and the piece grows over time. The growing magnitude of material, the accumulation of labor involved in dyeing and sewing each one echoes the way we as humans work hard to protect our denial and wild hopes around the unhealthy relationships in our lives. As it is ever changing and growing, this piece conforms to fit the space it is in. This references how we change in order to enable these relationships, which makes us too the red flag. Repetition allows for many interpretations. In Lost Love Letters, I address issues of loneliness and singularity through the telling of my experience finding letters from a former lover. The each one is independent of the others, but the three together speak about how our mind goes back again and again to things painful and confusing. The words are fading, coming unraveled. What are left are the promises, the words that lost their meaning first, but ones we held onto the longest. Because they are small and intricate, the viewer has to get up close to see the details and read the text. I do this to I create a private viewing experience. My color palate, fleshy pinks and bloody reds, seems to be drawn from the body, my body possibly. In Hope Chest I use "breast cancer pink" to remember my breast cancer treatment experience. Sickness is such a difficult thing for people to confront, yet it is one every one of us will face somehow. These needle-felted breasts are practically weightless; they are soft and pretty and inviting. I wanted to break down the fear of contamination and invite the viewer to feel something in reaction, instead of pushing it away. Because I address difficult topics, I have to create a safe space for the viewer. I do not intend to offend or shock. The words to talk about these issues have become whispers, barely audible. I give these subjects breath, and hope the viewer will give them voice. I use narratives of my personal experiences in my work. Because of this, the process of showing work is uncomfortable for me; I feel very vulnerable. I bring my stories to the viewer with honesty and compassion. But it is the sharing that is essential to the work I create. I don't consider my work done until it is shown. In Coming Out Dress, I transferred segments from my journal pages to the inside of the dress. The use of text speaks directly of communication. In my work the text is often obscured somehow. On the dress lining, it could only be read from the other side, but that cannot be seen because wrapping paper covers it. In Lost Love Letters III, the text is the same color as the handkerchief. In this way the words, the voices that speak the words, have been muted. This theme of obscured text in my work talks about the failing of words, how we are silenced, not heard, or how words have changing meanings and often betray us. I am influenced by the work of Jenny Holzer, who uses huge projections of words in site-specific light installations and repetition of phrases on light boards and signage. Her phrases are fragments of conversations. Taken out of context, they are open to new meanings and interpretations. The conflict between the internal and the external, or front and back, references my interest in the private and public spheres of society and its relationship to women and women's work. Domestic life, traditionally managed by women, is represented not only by my making processes like sewing, embroidery and, weaving; but also in the materials I use to make them. I am drawn to the things found in the linen closet. Blankets, sheets, tablecloths; these things speak of the day to day, of like inside the home and of who we are both personally and culturally. They are objects of the private life but they reflect the beliefs of society and gendered expectations about women and their roles and liberties. I bring my stories to the viewer with honesty and compassion.
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.